1991
DOI: 10.1002/polb.1991.090291106
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular structure investigation of poly(γ‐benzyl, α‐l‐glutamate)‐benzyl alcohol system by static light scattering

Abstract: The cholesteric mesophase of the PBLG‐BA system in concentrated solutions and in the gel phase has been investigated by static laser light scattering. The observed ‘distortion’ of the patterns in terms of their dependence on the azimuthal angle was studied. Effect of form‐optical rotation on the pattern is discussed. The manner of distortion in the Hv pattern determines the sense of cholesteric twisting. The observed scattering patterns are analogous to those obtained by previous investigators in other solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…Intermolecular association is not unusual for solutions of polyglutamates. In particular, association in dilute solutions of poly(γ-benzyl l -glutamate), PBG, has been explored by a variety of methods, to deduce both end-to-end and side-by-side association, depending on the conditions. Examples of other systems with potential relevance to this study occur in the intermolecular association frequently observed with solutions of heterocyclic semiflexible or rodlike chains. Some of these reveal thermally reversible changes in the electronic absorption as the nature of the intermolecular association changes over a narrow temperature range. ,,, With chains dissolved in strong protic acids, a change in the electronic absorption has been attributed in several cases to a decrease in the degree of protonation in the polymer as the aggregated structures collapse and organize to an ordered state, ,, similar to the process expected for semiflexible or rodlike polymers in concentrated solutions in poor solvents …”
Section: Introductionmentioning
confidence: 99%
“…Intermolecular association is not unusual for solutions of polyglutamates. In particular, association in dilute solutions of poly(γ-benzyl l -glutamate), PBG, has been explored by a variety of methods, to deduce both end-to-end and side-by-side association, depending on the conditions. Examples of other systems with potential relevance to this study occur in the intermolecular association frequently observed with solutions of heterocyclic semiflexible or rodlike chains. Some of these reveal thermally reversible changes in the electronic absorption as the nature of the intermolecular association changes over a narrow temperature range. ,,, With chains dissolved in strong protic acids, a change in the electronic absorption has been attributed in several cases to a decrease in the degree of protonation in the polymer as the aggregated structures collapse and organize to an ordered state, ,, similar to the process expected for semiflexible or rodlike polymers in concentrated solutions in poor solvents …”
Section: Introductionmentioning
confidence: 99%
“…The majority of the studies were concerned with flexible polymer chains that were crystallizable or contained stereoregular sequences . But semiflexible and rigid polymers had also been extensively studied; among the well-known examples were poly(γ-benzyl-α- l -glutamate), , poly(alkyl isocyanates), and polysaccharides . In this paper, we would like to report preliminary results on the gelation of three sulfonated rigid polymers, two of which were aromatic polyamides, and the third, a substituted poly( p -phenylene).…”
mentioning
confidence: 99%
“…However, rod-like polymers often form thermoreversible gels [1, 15, 16]. Many groups have shown that rod-like polymers have the ability to aggregate into microfibrils or nanofibers under specific solvent and temperature conditions [7, 8, 10, 17]. These nanofibers can be considered as supramolecular, flexible aggregates, whose formation is reversible.…”
Section: Introductionmentioning
confidence: 99%